Map of Critical Raw Material Deposits in Europe. (November 2016) - Bertrand, Guillaume; Cassard, Daniel; Arvanitidis, Nikolaos; Stanley, Gerry; ,
Abstract: The European Union aspires to reducing the import dependency of raw materials that are critical to its industries. In this respect, mineral resource information and data sharing by European Geological Surveys is crucial. In 2010, the European Commission identified 14 critical non-energy non-agricultural raw materials. This list was updated in 2014. This article presents the Critical Raw Material (CRM) Map of Europe produced by EuroGeoSurvey's Mineral Resources Expert Group. This map shows European mineral deposits from the EU FP7 ProMine project database, as containing critical commodities, according to the list of CRM published by the European Commission.